The Effectiveness Of Use Of Rewards And Punishments In The Stad Cooperative Learning Method To Increase Motivation And Science Learning Outcomes Of Class 4 Students Of Kolursari II SDN Bangil - Dewi Nurjannah; Devita Sulistiana; Dian Puspita Anggraini (JOSAR (Journal of Students Academic Research), 2025)
The importance of using Reward and Punishment as a stimulus to improve learning outcomes and student motivation. This research aims to determine the effect of using Rewards and Punishments on motivation and learning outcomes. This type of quasi-experimental research design is "pretest-posttest control group design". The research population was 40 students with a sample of 20 class IV A students as the experimental class and 20 class IV B students as the control class. The sampling technique uses saturated sampling. Motivation data collection uses a motivation questionnaire instrument and learning outcomes data collection uses a pretest-posttest learning outcomes instrument. Data analysis used the One Way Anova test. The research results of the use of Reward and Punishment on learning motivation obtained Fcount 23.37 > Ftable 4.10 with a sig level. 5% so H0 is rejected, meaning that the rewards and punishments given to the experimental class have a significant effect on student learning motivation. The research results of the use of Reward and Punishment on learning outcomes obtained Fcount 21.198 > Ftable 4.10 with a sig level. 5% so H0 is rejected, meaning that the rewards and punishments given to the experimental class have a significant effect on student learning outcomes. From this research, it can be concluded that the use of Rewards and Punishments in STAD type cooperative learning is effective in increasing the motivation and science learning outcomes of class IV students at SDN Kolursari II Bangil.